AUDIT SISTEM INFORMASI APLIKASI MY BEST DI UNIVERSITAS BINA SARANA INFORMATIKA MENGGUNAKAN COBIT 5 - Arif Rahman; Muhammad Syafickri Rhamzani, Wahyu Ningrat, Riza Fahlapi (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2024)
Information system audit is a critical activity to ensure that the information system operates according to the organization's needs, meets security standards, and minimizes the risk of failure or violations. COBIT 5 (Control Objectives for Information and Related Technologies) is a relevant framework for auditing the "My Best" application information system at Universitas Bina Sarana Informatika. The research method conducted by the author involved collecting responses from My Best application users via Google Forms and then calculating the maturity value of the My Best application using the COBIT 5 framework in the MEA domain. The research results show that MEA01 scored 3.90, MEA02 scored 3.79, and MEA03 scored 3.20. Thus, the gap or average result obtained from the overall scores is 3.63, compared to the desired value of 4.00.